Design and Implementation of a GaN-Based Composite Hybrid Switched-Capacitor DC-DC Converter for Space Applications - Samantha Coday; Elisa Krause; Margaret E. Blackwell; Rahul K. Iyer; Nathan M. Ellis; Ansel Barchowsky; Robert C.N. Pilawa-Podgurski (IEEE Open Journal of Power Electronics)
To enable next generation robotic space exploration, innovations in the area of high step-down voltage converters is necessary. This work explores the use of multilevel hybrid switched-capacitor power converters which have unique advantages in mass-critical and harsh radiation space environments. A composite converter topology is presented which utilizes two different hybrid switched-capacitor converters in a partial power processing system. First, a fixed-ratio capacitively-isolated resonant Dickson converter is designed for a high step-down conversion ratio and to process the majority of the system power. In addition, a flying capacitor multilevel (FCML) converter is designed to provide regulation over a wide range of input voltages. The optimization of each converter is discussed, with careful attention dedicated to the minimization of passive component mass. The hardware results for each converter and the full composite system are presented, showcasing a system efficiency of over 96% for a nominal 15:1 conversion ratio with regulation capability.